Peran Wakil Kepala Madrasah Bidang Kesiswaan dalam Pembinaan Kesiswaan di MTsN 6 CirebonN - Sutihatin, Sitiu - (IAIN Syekh Nurjati Cirebon, 2021)
ABSTRACTThe progress of a nation’s can be seen from the state of education. Students as the next generation of the nation need to get coaching to develop their knowledge, talents, and interests. This is certainly very good for the progress of the nation of Indonesia. Student development can be done through co-curricular and extracurricular activities. This research aims to determine the result of student coaching by the deputy of the student sector in carrying out his role, especially in developing and implementing a good student coaching program. Informants in this research were deputy of the student sector, students, and coaches or trainers of the extracurricular. This study used qualitative research method. So, to obtain information and data relating to the problem to be studied, researcher conducted observations, interviews, and documentations. The results of student coaching carried out through extracurricular activities can be quite good. Various competitions and championship that were followed, students of the madrasah often won. Even some students can continue their education to the next level through the achievement path, both academic and non-academic achievement. Keywords: The Role of the Deputy of Madrasah, Student Sector, Student Coaching. ABSTRAK Kemajuan peradaban suatu bangsa dapat dilihat dari keadaan pendidikannya. Siswa sebagai generasi penerus bangsa perlu mendapatkan pembinaan untuk mengembangkan pengetahuan, bakat dan minatnya. Hal ini tentu sangat baik bagi kemajuan bangsa Indonesia. Pembinaan kesiswaan dapat dilakukan melalui kegiatan kokurikuler dan ekstrakurikuler. Penelitian ini bertujuan untuk mengetahui hasil pembinaan kesiswaan oleh Wakil Kepala Madrasah bidang kesiswaan dalam melaksanakan perannya, terutama dalam menyusun dan melaksanakan program pembinaan kesiswaan yang baik. Informan dalam penelitian ini adalah Wakil Kepala Madrasah bidang Kesiswaan, siswa, dan pembina atau pelatih ekstrakurikuler. Penelitian ini menggunakan metode penelitian kualitatif. Jadi, untuk mendapatkan informasi maupun data yang berkaitan dengan masalah yang akan diteliti, peneliti melakukan obsevasi, wawancara, dan dokumentasi. Hasil dari pembinaan kesiswaan yang dilaksanakan melalui kegiatan ekstrakurikuler dapat dikatakan cukup baik. Berbagai perlombaan dan kejuaraan yang diikuti, siswa sering mendapat juara. Bahkan beberapa siswa dapat melanjutkan pendidikan ke jenjang berikutnya melalui jalur prestasi, baik prestasi akademik maupun non akademik. Kata kunci: Peran, Wakil Kepala, bidang Kesiswaan, Pembinaan Kesiswaan.